Extractive industries and development: Lessons from international experience for Mozambique - Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In common with several other low-income African economies, in recent years Mozambique has seen a significant expansion of interest and investment in its long-established extractives industries. Huge new gas finds in particular have led to expectations that these industries will contribute very significantly to the country's future economic development and structural change. However, the policy challenges associated with capturing the benefits of extractives activity and avoiding the well-documented downsides are numerous, and they embrace a wide range of areas of government policy, including macroeconomic, fiscal sectoral, environmental, and community aspects. This paper examines a wide range of these policy areas, and it attempts to summarize what we know from international experience about different policy approaches and some aspects of good practice as well as pitfalls. The paper is not intended as a set of policy prescriptions for Mozambique, but rather as a mapping of approaches in a wide set of relevant and interconnected policy areas, all of which will need careful consideration by the authorities in the months and years ahead.
Keywords: 330; Extractive industries; resource curse; policy coordination; institutional change; economic diversification; economic transformation